The delegated welfare state medicare, markets, and the governance of social policy - Morgan, Kimberly J., 1970-; Campbell, Andrea Louise, 1966- (New York ; Oxford : Oxford University Press, 2011)
'The Delegated Welfare State' tackles the federal government's increasing propensity in recent times to outsource governmental functions to the private sector.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human services -- Contracting out -- United States; Privatization -- United States; Welfare state -- United States; United States -- Social policy